Image Mosaicking Using Low-Distance High-Resolution Images Captured by an Unmanned Aerial Vehicle - Hassan, Faez M.; Mossa, Hussein Abdelwahab (Universitas Komputer Indonesia, 2021)
Regional surveys will have a high demand for coverage. To adequately cover a large area while retaining high resolution, mosaics of the area from a variety of scenes can be created. This paper describes a mosaicking procedure that consists of a series of processing steps used to combine multiple aerial images. These images were taken from CropCam unmanned aerial platform flight missions over the desired area to quickly map a large geographical region. The results of periodic processing can be compared and analyzed to monitor a large area for future research or during an emergency situation in the covered area. Digital imagery captured from the air has proven to be a valuable resource for studying land cover and land use. For this study, airborne digital camera images were chosen because they provide data with a higher spatial resolution for trying to map a small research area. On board the UAV autopilot, images were captured from an elevation of 320 meters using a standard digital camera. When compared to other airborne studies, this technique was less expensive and more cost effective. According to this study, onboard a UAV autopilot, a digital camera serves as a sensor, which can be helpful in planning and developing a limited coverage area after mosaicking